Methodology to map spatial variability of available nutrients in area of intensively growing potato (Solanum tuberosum) using remote sensing and GIS - KUMAR, MANOJ; JATAV, M K; DUA, V K; TREHAN, S P; LAL, S S; UPADHYAY, N C (The Indian Journal of Agricultural Sciences, 2014)
A methodology is developed for mapping spatial variability of available nutrients of soils of a pocket growing potato (Solanum tuberosum L.) crop using GIS. For this purpose potato growing pockets of the Jalandhar district were demarcated based on the available information, ground truth and classification of the IRS P6 AWiFS image. The classified potato area in the image was taken as background to generate the sampling site map and representative soil samples of potato fields from these sites were collected along with geographical coordinates using GPS receiver(ETREX-VISTA, Garmin). Values of different parameters (like pH, OC, available P and K and micronutrients) were tagged with corresponding points and interpolation maps for each individual parameters were prepared using suitable semivariogram and kriging in remote sensing GIS software. These prepared maps were further classified giving suitable ranges of different soil parameters.